Usefulness of bioelectrical impedance analysis in assessment and monitoring of nutrition status of chronic heart failure patients - Sobieszek, Grzegorz; Skwarek-Dziekanowska, Aneta; Kot, Agata; Rahnama-Hezavah, Mansur; Powrózek, Tomasz; Małecka-Massalska, Teresa (Medical Studies/Studia Medyczne, 2024)
In chronic heart failure (CHF) patients malnutrition and/or cachexia are frequently observed syndromes that negatively affect the quality of life and survival of patients. That makes it necessary to investigate reliable methods of assessment of body composition which can facilitate appropriate clinical decisions on patients’ treatment. Bioelectrical impedance analysis (BIA) is a reliable and non-invasive method to test body composition in patients suffering from various chronic diseases, including CHF. The aim of the review was to summarize recent findings on BIA assessment for nutritional and clinical management of CHF. Although BIA is a known technique used for body composition assessment, the number of papers analyzing its utility in cardiovascular diseases is still limited, particularly with a combination of molecular markers. Electrical parameters obtained in BIA in conjunction with biochemical determinations and molecular factors can improve selection of patients at risk of malnutrition and unfavorable prognosis related to nutritional deficits.